Fine‐needle biopsy with 19G needle is effective in combination with endoscopic ultrasound‐guided tissue acquisition for genomic profiling of unresectable pancreatic cancer. Issue 1 (13th September 2022) - Ikeda, Go; Hijioka, Susumu; Nagashio, Yoshikuni; Maruki, Yuta; Ohba, Akihiro; Hisada, Yuya; Yoshinari, Motohiro; Harai, Shota; Kitamura, Hidetoshi; Koga, Takehiko; Murashima, Yumi; Maehara, Kosuke; et al.
Abstract : Objectives: Comprehensive genomic profiling (CGP) has been approved in Japan since June 2019, enabling mutation‐specific therapy. Although tissue sampling via endoscopic ultrasound‐guided tissue acquisition (EUS‐TA) is standard in pancreatic cancer, reports on obtaining appropriate samples for CGP, especially for the OncoGuide NCC Oncopanel System (NOP) and FoundationOne CDx (FOne), are lacking. Therefore, we investigated the success rate and factors related to appropriate EUS‐TA sampling for CGP analysis suitability in unresectable pancreatic ductal adenocarcinoma (UR‐PDAC). Methods: Participants comprised 150 UR‐PDAC patients who underwent EUS‐TA and tumor sample evaluation for CGP analysis suitability between June 2019 and December 2021. The proportion of patients meeting the criteria was evaluated considering tumor size, puncture lesion, presence of metastasis, type and size of puncture needle, suction method, number of punctures, and puncture route. Results: In total, 39.2% (60/153) of samples met NOP analysis suitability criteria and 0% met FOne analysis suitability criteria. The suitability rate was significantly higher with 19G fine‐needle biopsy (FNB) (56.0%; 42/75) than with 22G FNB (32.6%; 14/43) and 22G fine‐needle aspiration (11.4%; 4/35). Nineteen‐gauge needle (odds ratio [OR] 2.53; 95% confidence interval [CI] 1.15–5.57; P = 0.021) and FNB (OR 3.57; 95% CI 1.05–12.20; P = 0.041) were independent factors contributing to NOP analysis suitability. Among 30 patients who underwent actual NOP analysis, the analysis success rate was 100% (30/30). Conclusion: In sample collection via EUS‐TA, 19G and FNB needles contribute to NOP analysis suitability.